Degenerate and Singular Differential Operators with Applications to Boundary Value Problems. (2nd March 2011) - Alves Alves, Claudianor Oliveira Claudianor Oliveira; Rădulescu Rădulescu, Vicenţiu Vicenţiu
Abstract :